IMPLEMENTASI SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE DALAM PEMILIHAN MINAT EKSTRAKURIKULER SISWA - Firamon Syakti; Baibul Tujni (IIB Darmajaya, 2020)
Extracurricular activities are part of the internal learning process of schools as an effort to channel talent as a driver of fulfillment and student development. Among the extracurricular activities at school are (1) scouts, (2) Paskibraka, (3) Red Cross, (4) School security forces, (5) Nature lovers, (6) School health, (7) Scientific Youth, (7) 8) Sports, and (9) Arts. The choice of extracurricular interests is an important factor for students. The right choice will have an impact on improving the ability and skills of students themselves. For this reason, in this study the SMART method was implemented that could assist students in selecting extracurricular activities that they would like to do. The implementation of the SMART method is carried out by means of or through decision support information systems. The decision support information system development is using the waterfall method which has five stages, namely communication, planning, modeling, construction and deployment. The results of the development show that the resulting information system can run the SMART method correctly starting from charging the value of interest, weighting, utility, and gritting. These conditions can also be seen from the results of tests that show all components can be accepted or functionaly.